The Impact of the 2018 Kerala Floods on Butterfly Diversity and Abundance in the Kollam District of India - Sudhakaran, Bindu Vijayakumari; Shifana, B. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Kerala experienced flooding in August 2018 as actual rainfall there exceeded expected rainfall. The current study was carried out in Kerala, India's Kollam district, between September 2018 and August 2019. The survey was carried out at four sites, namely hilly areas, wetlands, plains and homestead vegetation. In the current study, 72 butterfly species from five families were identified. The family Nymphalidae is the dominant butterfly family with 38 species, followed by Lycaenidae with 12 species, Papilionidae with 10 species, Pieridae with eight species and Hespiridae with four species. Of these, six butterfly species were very common, 23 species were common and 21 species were occasional, 19 species were rare and three species were very rare. Various diversity indices such as the Berger-Parker index, Margalef index, Simpson index -λ, Simpson index -D, Simpson index -Dr, Shannon index and Pielou index are calculated. Environmental impoverishment will greatly affect the survival of these beautiful creatures as they are very sensitive to changes in the environment.